(untitled) (Universal International Scientific Journal, 2026)
This article theoretically analyzes the essence of family values, their current state, and strategies aimed at preserving and strengthening them in the context of information threats. The negative impact on the institution of the family in an era of rapid expansion of the information space is studied, the issues of conflict between traditional values ​​and modern information flows are considered. The role of family values ​​in social stability is substantiated, and the educational, spiritual, and social mechanisms that serve to preserve them are consistently described. The article evaluates the impact of the information environment on family education from the point of view of national and universal values.